2017
DOI: 10.1542/peds.2016-3823
|View full text |Cite
|
Sign up to set email alerts
|

Partnerships for Global Child Health

Abstract: Child mortality remains a global health challenge and has resulted in demand for expanding the global child health (GCH) workforce over the last 3 decades. Institutional partnerships are the cornerstone of sustainable education, research, clinical service, and advocacy for GCH. When successful, partnerships can become self-sustaining and support development of much-needed training programs in resource-constrained settings. Conversely, poorly conceptualized, constructed, or maintained partnerships may inadverte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 52 publications
(43 reference statements)
1
55
0
Order By: Relevance
“…40 Another study suggested that benefits of academic global health partnerships include publication of research, innovation and problem-solving from different perspectives, alliances promoting social justice, and enhanced capacity to scale-up effective interventions. 41 Although respondents in our study believed such partnerships to be beneficial overall, some respondents reported challenges in academic global health collaborations. Specifically, LMIC † Other reasons included "they were more insightful than other team members and able to define the research agenda consistent with national priorities" (n = 1), "they had to comply with their organization's rules" (n = 2), "often researchers from HICs use ideas, research questions, and even protocols that arise in low-income countries which then use them to promote their own research agenda" (n = 1), "the LMIC is used merely as a data source" (n = 1), "they were only interested in data and not true capacity building" (n = 1), and "they had a condescending attitude and did not sufficiently value the input from researchers in the low-income country" (n = 1).…”
Section: Discussionmentioning
confidence: 66%
“…40 Another study suggested that benefits of academic global health partnerships include publication of research, innovation and problem-solving from different perspectives, alliances promoting social justice, and enhanced capacity to scale-up effective interventions. 41 Although respondents in our study believed such partnerships to be beneficial overall, some respondents reported challenges in academic global health collaborations. Specifically, LMIC † Other reasons included "they were more insightful than other team members and able to define the research agenda consistent with national priorities" (n = 1), "they had to comply with their organization's rules" (n = 2), "often researchers from HICs use ideas, research questions, and even protocols that arise in low-income countries which then use them to promote their own research agenda" (n = 1), "the LMIC is used merely as a data source" (n = 1), "they were only interested in data and not true capacity building" (n = 1), and "they had a condescending attitude and did not sufficiently value the input from researchers in the low-income country" (n = 1).…”
Section: Discussionmentioning
confidence: 66%
“…Additionally, evaluation in GCH education could be strengthened through more multiinstitutional evaluations. Collaborations with initiatives such as the Association of Pediatric Program Directors Longitudinal Educational Assessment Research Network, which supports 4 These evaluations allow other programs to replicate successful approaches.…”
Section: Possible Approaches To Address Evaluation Needsmentioning
confidence: 97%
“…3 In clinical practice, there are growing numbers of LMIC-HIC clinical partnerships, which provide clinical care and support mutual professional development. 4 There are also expanding opportunities for HIC clinicians to participate in short-term medical trips. 5 In research, there are increasing partnerships and networks supporting collaborative transnational GCH research.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing recognition of the severity of the tropical diseases affecting children in developing nations, as well as among the poor living in wealthy countries, including the US, Europe, and Australia [33], should we consider reassessing the overall framework of pediatric tropical medicine? In 2017, the Global Health Task Force of the American Board of Pediatrics (ABP) outlined mechanisms of how partnerships might advance global child health and health systems, with an emphasis on seven “guiding principles”—equity, sustainability, mutual benefit, humility, inclusivity, social justice, and prevention of adverse impact—and four “core practices” of communications, leadership, conflict resolution, and evaluation [34]. Under this rubric, at least one way to proceed in the US might include building on our existing pediatric infectious diseases fellowship programs and adding, as a stackable credential, one of the several diploma or certificate courses in tropical medicine (and in-country experiences) that currently lead to certification by the American Society of Tropical Medicine and Hygiene (ASTMH) [35].…”
Section: An Expanded Frameworkmentioning
confidence: 99%